2017
DOI: 10.1080/09168451.2017.1353403
|View full text |Cite
|
Sign up to set email alerts
|

Astilbe thunbergii reduces postprandial hyperglycemia in a type 2 diabetes rat model via pancreatic alpha-amylase inhibition by highly condensed procyanidins

Abstract: Type 2 diabetes mellitus (T2DM) is a common global health problem. Prevention of this disease is an important task, and functional food supplements are considered an effective method. We found potent pancreatic α-amylase inhibition in Astilbe thunbergii root extract (AT) and confirmed that AT treatment in a T2DM rat model reduces post-starch administration blood glucose levels. Activity-guided isolation revealed procyanidin (AT-P) as the α-amylase inhibitory component with IC = 1.7 μg/mL against porcine pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…However, in some cases, high levels of blood glucose due to excess activity of alpha-amylase results in hyperglycemia [15]. Thus, the inhibition of alpha-amylase activity can reduce postprandial hyperglycemia and prevent the risk of diabetes development [16,17]. In this study, ethanol extract of M. indica leaves (MIL) was investigated for its capability against alpha-amylase activity.…”
Section: Alpha-amylase Inhibitory Activitymentioning
confidence: 99%
“…However, in some cases, high levels of blood glucose due to excess activity of alpha-amylase results in hyperglycemia [15]. Thus, the inhibition of alpha-amylase activity can reduce postprandial hyperglycemia and prevent the risk of diabetes development [16,17]. In this study, ethanol extract of M. indica leaves (MIL) was investigated for its capability against alpha-amylase activity.…”
Section: Alpha-amylase Inhibitory Activitymentioning
confidence: 99%
“…Notably, α-amylase enzyme plays an important role in carbohydrate digestion and postprandial glucose increase in diabetic patients. Thus, the inhibition of α-amylase activity can reduce postprandial hyperglycemia and prevent the risk of diabetes [28,29]. Recently, wild bitter melon has been emerged as an alternative medicine for prevention and/or treatment of type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-amylase assay resulted in the inhibition of AERM activity at an IC 50 of 19.0 µg/mL, while acarbose inhibited amylase with an IC 50 of 5.2 µg/mL ( Figure 8 ). Tannins have been suggested as potent inhibitors of human salivary and porcine pancreatic α-amylases [ 34 , 35 ], suggesting that PAs from AERM could be implicated in this potent inhibitory activity. In addition, it has been reported that PAs of cinnamon water extract inhibited the amyloid formation of Human islet amyloid polypeptide (hIAPP) in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%